The masking and making of fieldworkers and data in postcolonial global health research contexts - Kingori, P; Gerrets, R (Taylor & Francis (Routledge), 2019)
This paper centres on the roles and contributions of fieldworkers-local data-collectors in Global Health research in postcolonial contexts. It is informed by two separate ethnographies, conducted in two different East African biomedical research institutions. It discusses how common characterisations of fieldworkers as ‘low-skilled’ and ‘local’ make them attractive to research institutions in two important ways – as community-embedded data-collectors thus facilitating community participation and as being unlikely to fabricate data because they lack the skills to avoid detection. This paper questions these assumptions. It draws on Daston’s idea of the ‘scientific persona’ and Fanon’s concepts of mask-making to explore how fieldworkers construct identities and data within their liminal roles. Fieldworkers create particular pseudo-personae or masks for getting and staying employed. They dumb-down CVs and emphasise their similarities with community members in ways which are partially ‘real’ but also ‘fake’. These constructed identities provide fieldworkers with a persona that allows them to fabricate or modify data without raising suspicions. They frequently engage in practices known as ‘genuine fake’ data fabrication which is data perceived as factually correct and verifiable yet methodologically incorrect, hence it is real and fake in varying degrees. We understand the ‘pseudo’ as the blurry space between real and fake where fieldworkers construct their identities and data. Given the seemingly laudable aims of Global Health, we argue that fieldworkers’ masking and making up data signal the need for greater attention by those designing its research, to better understand and address why and how these practices unfold.